The Relationship Between COVID-19 Disease Knowledge Level and Sociodemographic Characteristics and Fear of COVID-19: A Cross-Sectional Study - Yalnız Dilcen, Hacer; Bulut, Ebru; Önal, Yakup; Yılmaz, Fatih; Taşkaya, Zehra; Dilcen, Hacer Yalnız; Bulut, Ebru (My University, 2023)
Objective: The coronavirus disease-2019 (COVID-19) pandemic has adversely affected human life in many ways. This study was conducted to determine the relationship between the level of knowledge of COVID-19 disease, sociodemographic characteristics and fear of COVID-19. Material and Methods: This study is a cross- sectional research conducted on the web. 498 participants were included in the analysis after the sample with incomplete data entry and dis- rupting the normal distribution was removed. Data collection tools were sent to the participants via an online questionnaire link. Statistical data were evaluated with independent t-test, one-way analysis of variance, correlation and regression analysis by using SPSS 24 package program. Results: The mean age of the 498 participants included in the analysis in the study was 29.52 (minimum=18, maximum=72), and it was de- termined that 59.6% were women and 50% were associate degree grad- uates. The fear of COVID-19 is higher in women, those over 65, those with chronic diseases and those who perceive COVID-19 disease as a life threatening . It has been determined that there is a statistically sig- nificant, positive and weak relationship between individuals' fear of COVID-19 and gender, number of children, and a negative and strong relationship between COVID-19 disease threatens life and gender. When the regression analysis results are examined; when the signifi- cance of the variables used in the model was examined, it was found that the age and gender of COVID-19 disease was statistically signifi- cant for life threatening (p<0.05). Conclusion: It was found that the level of knowledge and fear of COVID-19 were not correlated, and that sociodemographic characteristics were related to the fear of COVID-19.
Keywords: Hemşirelik; Psikoloji; COVID-19; knowledge; fear